Immunohistochemical expression of Fas/Fasligand and c-Myc in oral lichen planus - Abdul-Razzaq A M Wahhab; Riyadh O Alkaisi (Journal of Baghdad College of Dentistry, 2014)
Background: Oral Lichen Planus is a chronic inflammatory mucosal disease, presenting in various clinical forms .Both antigen-specific and non-specific mechanisms involved in the pathogenesis of OLP. Apoptosis or programmed-cell death is a physiological process essential for the normal development and maintenance of homeostasis in many organisms. Fas is a cell-surface glycoprotein, 40-kDa, that belongs to the nerve growth factor / tumor necrosis factor (TNF) receptor family. Fas is expressed in several tissues including blood, where its expression is upregulated on activated T and B lymphocytes and natural killer cells. Fas ligand is a type II transmembrane protein that belongs to the tumor necrosis factor family. The proto-oncogene c-Myc is a transcripation factor with roles in cellular proliferation, differentiation, apoptosis and cell cycle progression. Mutation in the c-Myc gene and protein over-expression has been associated with a variety of hematopoietic tumors, leukemias and lymphomas. Apoptosis is the mechanism that would be dysregulated in this disease. This study was conducted to evaluate the expression of Fas, Fasl and c-Myc in oral lichen planus and to correlate the expression of either markers with each other. Materials and Methods: This study was performed on thirty formalin- fixed paraffin-embedded tissue blocks of oral lichen planus pro and retrospectively. An immunohistochemical staining was done by using monoclonal antibodies for Fas, Fasl and c-Myc. Results: Expressions of Fas, Fasl and c-Myc were highly detected in keratinocytes and inflammatory cells of OLP cases compared to negative expression in normal oral mucosa. Significant correlation has been found between expression of Fas, Fasl and c-Myc in epithelial cells with that of inflammatory cells in oral lichen planus studied cases. Significant correlation has been found among expressions of Fas, Fasl and c-Myc in epithelial cells of oral lichen planus cases. Significant positive correlation found between expressions of Fas, Fasl and c-Myc in keratinocytes and inflammatory cells of oral lichen planus . Conclusion: Increased expression level of Fas, Fasl and c-Myc in both keratinocytes and lymphocytes of OLP cases in comparison to normal mucosa with highly significant correlation among the markers expression indicate their important role in malignant transformation of oral lichen planus.